1982
DOI: 10.2136/sssaj1982.03615995004600040030x
|View full text |Cite
|
Sign up to set email alerts
|

Perched Water Tables on Hillsides in Western Oregon: I. Some Factors Affecting Their Development and Longevity

Abstract: Perched water tables on hillsides located on the western border of the Willamette Valley in Oregon in some cases have the potential to transport pollutants from either domestic or agricultural sources downslope to streams, ponds, or reservoirs, resulting in the deterioration of the quality of these waters. In this paper, some factors responsible for the development and longevity of these potentially problem‐causing perched water tables on three hillsides were examined. Analyses of hydraulic conductivity data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Although clearly present at the field scale [ Getzen , 1983; Garabedian et al , 1988; LeBlanc et al , 1988; Killey and Moltyaner , 1988], a high degree of anisotropy at the laboratory scale has not been demonstrated on measurements from individual core samples. Laboratory measurements of vertical and horizontal hydraulic conductivity on porous media from a wide range of geologic materials and soils show a low degree of anisotropy with a ratio near 1 [ Pryor , 1973; Hammermeister et al , 1982; Yasuike et al , 1987; Burger and Belitz , 1997].…”
Section: Unsaturated Zone Flow Modelmentioning
confidence: 99%
“…Although clearly present at the field scale [ Getzen , 1983; Garabedian et al , 1988; LeBlanc et al , 1988; Killey and Moltyaner , 1988], a high degree of anisotropy at the laboratory scale has not been demonstrated on measurements from individual core samples. Laboratory measurements of vertical and horizontal hydraulic conductivity on porous media from a wide range of geologic materials and soils show a low degree of anisotropy with a ratio near 1 [ Pryor , 1973; Hammermeister et al , 1982; Yasuike et al , 1987; Burger and Belitz , 1997].…”
Section: Unsaturated Zone Flow Modelmentioning
confidence: 99%
“…Agricultural plough pans at depths between 10 cm and 20 cm are common (Burwell and Larson, 1969;China et al, 1985;Michiels et al, 1989), and studies have found perched water tables on agricultural soils from Europe (Poesen, 1981) to Australia (George and Conacher, 1993). Perched water tables have also been found within 15 cm of the surface in Typic Torriorthent soils in semi-arid SE Spain (Puigdefabregas et al, 1998), above impermeable bedrock in Oregon, USA (Hammermeister et al, 1982), within 8-23 cm of the surface on a forested clayey hillslope in Luxembourg (Cammeraat, 1992), and above silt-clay deposits in the UK (Brown and Bradley, 1995).…”
Section: Soil Depth and The Capillary Fringementioning
confidence: 99%
“…While this study provides an analogue of agricultural soils above a plough pan, thin soils above impermeable rock or other layers are also likely to develop water tables during rainstorms (Hammermeister et al, 1982). At larger scales this may be especially common where antecedent moisture is high, such as near the base of slope or in cross-slope hollows.…”
Section: Geomorphological Implicationsmentioning
confidence: 99%
“…Beven and Germann (1981) summarized the effect of these factors in the field by describing the initiation of macropore flow as the result of one of two conditions: either when rainfall intensity exceeds the maximum infiltration rate of the soil matrix; or when the soil matrix becomes saturated. Thus macropore flow can occur from the soil surface under saturated (McDonnell, 1990;Wilson et al, 1997) or unsaturated matrix conditions (Hammermeister et al, 1982;Jardine et al, 1989;Wilson et al, 1997) or be initiated at depth in the soil profile at a site of discontinuity in the soil structure (Heppell et al, 2000a, b). The horizontal and lateral connectivity of the macropore system itself is also an important factor controlling the extent of macropore flow in a soil.…”
Section: Introductionmentioning
confidence: 99%